Antibody Conjugates for Targeted Therapy Against HIV-1 as an Emerging Tool for HIV-1 Cure - Umotoy, Jeffrey C.; de Taeye, Steven W. (Frontiers in Immunology, 2021)
Although advances in antiretroviral therapy (ART) have significantly improved the life expectancy of people living with HIV-1 (PLWH) by suppressing HIV-1 replication, a cure for HIV/AIDS remains elusive. Recent findings of the emergence of drug resistance against various ART have resulted in an increased number of treatment failures, thus the development of novel strategies for HIV-1 cure is of immediate need. Antibody-based therapy is a well-established tool in the treatment of various diseases and the engineering of new antibody derivatives is expanding the realms of its application. An antibody-based carrier of anti-HIV-1 molecules, or antibody conjugates (ACs), could address the limitations of current HIV-1 ART by decreasing possible off-target effects, reduce toxicity, increasing the therapeutic index, and lowering production costs. Broadly neutralizing antibodies (bNAbs) with exceptional breadth and potency against HIV-1 are currently being explored to prevent or treat HIV-1 infection in the clinic. Moreover, bNAbs can be engineered to deliver cytotoxic or immune regulating molecules as ACs, further increasing its therapeutic potential for HIV-1 cure. ACs are currently an important component of anticancer treatment with several FDA-approved constructs, however, to date, no ACs are approved to treat viral infections. This review aims to outline the development of AC for HIV-1 cure, examine the variety of carriers and payloads used, and discuss the potential of ACs in the current HIV-1 cure landscape.